Estimating Nitrogen Use Efficiency, Profitability, and Greenhouse Gas Emission Using Different Methods of Fertilization - Nasrullah, Muhammad; Liang, Lizhi; Rizwanullah, Muhammad; Yu, Xiuyuan; Majrashi, Ali; Alharby, Hesham F.; Alharbi, Basmah M.; Fahad, Shah (Frontiers in Plant Science, 2022)
Fertilization is a way to better use nitrogen fertilizers and increase productivity, but in another way, fertilization is also a source of anthropogenic greenhouse gas emissions. The study was carried out to measure the profitability ratio, technical efficiency and CO2 from the top dressing (TD) and deep placement (DP) fertilization. The study was based on primary data, which was collected from different respondents and areas through a well-designed questionnaire. The study finds that DP fertilization is more profitable, least costly and more efficient than TD fertilization. The finding observed that the yield of the TD growers is 727.82 kg/ha more than that of TD respondents. The efficiency score shows that to reach the 90% efficiency level, the farmers of TD need to use DP fertilization. The farmers of TD and DP can still increase their efficiency up to 12 and 9% by using the same inputs. The findings also clarify that manufacturing of synthetic nitrogen (N), direct use of N, Yield and Area-Scaled greenhouse gas (GHG) emissions from the use of synthetic N through TD fertilization is greater than that of the DP group. The farming community needs to be aware of greenhouse gas emissions and how they can be reduced. It is also suggested that farmers need to shift toward DP fertilization to increase yield, profit, efficiency, food security and reduce GHG emissions.